2020
DOI: 10.21203/rs.3.rs-42143/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improvement of stem cell-derived exosome release efficiency by surface-modified nanoparticles

Abstract: Background: Mesenchymal stem cells (MSCs) are pluripotent stromal cells that release extracellular vesicles (EVs). EVs contain various growth factors and antioxidants that can positively affect the surrounding cells. Nanoscale MSC-derived EVs, such as exosomes, have been developed as bio-stable nano-type materials. However, some issues, such as low yield and difficulty in quantification, limit their use. We hypothesized that enhancing exosome production using nanoparticles would stimulate the release of intrac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
(51 reference statements)
0
11
0
Order By: Relevance
“…For this reason, it is crucial to isolate highly purified exosomes secreted from MSCs without contaminants. For clinical applications, various attempts to standardize on the method of separating exosome and culturing the cells have been reported for increasing production yield and purity of exosomes [47][48][49][50][51]. Especially, the types of media used for cell culture play an important role not only in determining the state of cells, but also in determining the properties of exosomes secreted from the cells.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is crucial to isolate highly purified exosomes secreted from MSCs without contaminants. For clinical applications, various attempts to standardize on the method of separating exosome and culturing the cells have been reported for increasing production yield and purity of exosomes [47][48][49][50][51]. Especially, the types of media used for cell culture play an important role not only in determining the state of cells, but also in determining the properties of exosomes secreted from the cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, previously reports showed excellent therapeutic potential efficacy with application in EVs through bioengineering techniques such as cargo loading and surface modification [84,85]. The low EV yield and the lack of the ability to target specific organs or molecules are two disadvantages associated with the use of EV; however, these limitations can be overcome by international regulation [77,78]. In addition, clinical research using EVs will be accelerated by the development of 3D culture technology and increasing the yield of EVs by the use of bioreactors [93,94].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our research team has developed a technology that can increase the number of EVs generated from stem cells by approximately 100 times by using iron oxide nanoparticles with a positive surface charge [78]. It was found that the components of the obtained exosomes contained miRNA factors related to proliferation, anti-inflammatory, and ROS reduction.…”
Section: Study On Nerve Kidney Liver and Lung Tissue Regenerative Therapymentioning
confidence: 99%
“…Finally, exposition of cells to several types of exogenous particles have also been reported to increase EV secretion. Internalization of positively charged iron oxide nanoparticles encapsulated in PLGA-PEI polymer by MSCs increased secretion of extracellular vesicles, which appeared to be linked to increased autophagosome formation 85 . In Emam et al 86 , four cancerous cell lines were incubated for 48 h with different concentration of neutral, cationic-bare or PEGylated liposomes solutions.…”
Section: Stimulating Cells To Increase Ev Yield 41 Physical and Chemical Stimulationmentioning
confidence: 94%